2014
DOI: 10.1016/j.fuel.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of direct injection timing of ethanol fuel on engine knock and lean burn in a port injection gasoline engine

Abstract: Improving engine efficiency and reducing its emissions are the major tasks of recent development in internal combustion technology [1]. This is driven by the society concerns about the global warming and the depletion in supply of fossil fuels. One of the feasible short-to-midterm solutions for addressing the concerns is to use renewable fuels such as ethanol. Many countries and areas have enacted legislations [2] or incentive policies to promote the use of ethanol and other bio/renewable fuels [3,4]. The use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 30 publications
3
26
0
1
Order By: Relevance
“…In high-velocity flows, the effect of convective flow on taking the evaporating material from the droplet surface to the bulk gas phase becomes significant. and 250 CAD BTDC in the engine experiments, as reported in [31]. The lower evaporation rate of late EDI injection has significant effect on the following combustion process.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In high-velocity flows, the effect of convective flow on taking the evaporating material from the droplet surface to the bulk gas phase becomes significant. and 250 CAD BTDC in the engine experiments, as reported in [31]. The lower evaporation rate of late EDI injection has significant effect on the following combustion process.…”
Section: Resultssupporting
confidence: 61%
“…Experimental results showed that late EDI timing allowed more advanced spark timing without knock issue than early EDI timing did, but also deteriorated the combustion and emission performance of the engine [31]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…2 First proposed by Ikoma et al [22], such systems provide more flexibility in terms of control, particle reduction and knock suppression [23][24][25][26] and are currently used in GDI engines [14].…”
Section: Development Of Gdi Combustion Systemsmentioning
confidence: 99%
“…The complexity is arguably further exacerbated by emerging future fuels, where a fuel such as ethanol with high sensitivity (i.e. relatively high RON but low MON) may help reduce the onset of knock [1,[33][34][35] but could theoretically exacerbate sporadic pre-ignition under certain conditions due to the increased pre-ignition tendency as indicated by the lower MON rating [36].…”
Section: Introductionmentioning
confidence: 99%